Ancaman Krisis Petani Di Indonesia Berdasarkan Hasil Sensus Pertanian 2023 - Noor, Rillando Maranansha; Suwandana, Endan (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2024)
Abstract. Indonesia’s growing population creates high demand for food production and agricultural labor. Research shows a worrying trend: the number of farmers is declining, as the number of farmers ages and there is a lack of younger replacements. The study analyzed data from the 2023 Agricultural Census, which showed that almost 40% of farmers are over 55 years old, while millennials (aged 19-39) only make up 21%. The number of Individual Farming Enterprises (UTP) has decreased from 31.70 million in 2013 to 29.34 million in 2023. To ensure sustainable food security, the government needs to implement policies that attract young people to enter the agricultural sector. This could include measures such as income stability, infrastructure improvements, and import regulations that protect farmers’ livelihoods. Encouraging a new generation of “millennial farmers” is critical to Indonesia’s future food security. Keywords: Agriculture Census, Agriculture Workforce, Farmer Aging, Millennial Farmers, Regeneration Farmer